Kepatuhan dan Ketepatan Tenaga Medis dalam Pengisian Assessment Pre Dialisis di Klinik Hemodialisis Nitipuran Health Center - Raditya Priambodo; Elsye Maria Rosa; Sri Sundari (Universitas Batanghari Jambi, 2020)
Background: The National Hospital Accreditation Standards (SNARS) state that one of the key indicators in patient-focused service standards is patient assessment. The purpose of this study was to analyze the level of compliance and accuracy of medical personnel in pre dialysis assessments at NHC. Subjects and Method: This study uses a mixed method with the Cohort Study approach. Research subjects were medical records for quantitative data and doctors, nurses and head nurses for qualitative data. Quantitative data analysis with descriptive analysis, and qualitative analysis with in-depth interviews. Result: The level of compliance and accuracy of medical personnel in filling the pre dialysis assessment at the Nitipuran Hemodialysis Clinic is not quite good. The implementation of pre dialysis assessment at the NHC includes physical status, medical history, history of drug allergy, assessment of pain, risk of falls, and educational needs. Constraints include time constraints, assessments are filled in immediately without checking in detailly, there are gaps in the hourly monitoring records. Conclusion: compliance and accuracy of medical personnel in filling out assessments must be improved.